2020
DOI: 10.2298/psi190520017s
|View full text |Cite
|
Sign up to set email alerts
|

Association between maladaptive sleep hygiene behaviors and sleep quality in the general population

Abstract: Prevalence of sleep problems has grown globally in recent years and sleep hygiene recommendations have shown inconsistent results. This study aims to analyze the quality of sleep in a non-clinical population and its association with maladaptive sleep hygiene. A total of 465 participants, with median age of 35 years (Interquartile range-IQR = 28-44), completed the Sleep Hygiene Practices Scale (SHPS) and the Pittsburgh Sleep Quality Index (PSQI). Sample was divided into good quality sleepers (GQS; 52.7%, n = 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Social media use has previously been identified as a risk factor for sleep disorders (Bhat et al, 2018). Previous research has also demonstrated that the quality of sleep is highly connected with the cognitive activity that occurs before bedtime (Sancho-Domingo et al, 2020). Furthermore, it has been suggested that using social media closer to bedtime is associated with increased cognitive arousal, resulting in delayed sleep latency and difficulty maintaining sleep (Thomée et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Social media use has previously been identified as a risk factor for sleep disorders (Bhat et al, 2018). Previous research has also demonstrated that the quality of sleep is highly connected with the cognitive activity that occurs before bedtime (Sancho-Domingo et al, 2020). Furthermore, it has been suggested that using social media closer to bedtime is associated with increased cognitive arousal, resulting in delayed sleep latency and difficulty maintaining sleep (Thomée et al, 2010).…”
Section: Introductionmentioning
confidence: 99%